COVID-19, Social Isolation, and Mental Health Among Older Adults: A Digital Catch-22 - Cosco, Theodore D; Fortuna, Karen; Wister, Andrew; Riadi, Indira; Wagner, Kevin; Sixsmith, Andrew (JMIR Publications, 2021)
One of the most at-risk groups during the COVID-19 crisis is older adults, especially those who live in congregate living settings and seniors' care facilities, are immune-compromised, and/or have other underlying illnesses. Measures undertaken to contain the spread of the virus are far-reaching, and older adults were among the first groups to experience restrictions on face-to-face contact. Although reducing viral transmission is critical, physical distancing is associated with negative psychosocial implications, such as increased rates of depression and anxiety. Promising evidence suggests that participatory digital co-design, defined as the combination of user-centered design and community engagement models, is associated with increased levels of engagement with mobile technologies among individuals with mental health conditions. The COVID-19 pandemic has highlighted shortcomings of existing technologies and challenges in their uptake and usage; however, strategies such as co-design may be leveraged to address these challenges both in the adaptation of existing technologies and the development of new technologies. By incorporating these strategies, it is hoped that we can offset some of the negative mental health implications for older adults in the context of physical distancing both during and beyond the current pandemic.